Bridging gaps, saving lives: integrating communities’ voices and impact mapping into flood early warning systems in rural Nepal - Shrestha, A.; McCrone, A.; Lang-Ritter, J.; Gautam, S.; Taka, M.; Varis, O. (Elsevier, 2025)
Flood risks and impacts on population are expected to escalate globally especially where flood forecasting and warning capabilities are limited. Establishing an effective link between early warning and early actions can mitigate flood risks. Yet, scientific methods to strengthen this link remain scarce, as highlighted by common practical challenges: 1) Insufficient integration of scientific spatial risk information in existing early action protocols and disaster preparedness plans, and 2) Inadequate consideration of challenges faced by vulnerable rural communities affecting practical implementation of the plans. By the example of the West Rapti River Basin in rural Nepal, this interdisciplinary study addresses these gaps through developing a mixed-method approach consisting of three steps. First, with empirical community survey and key informant interview data, we investigate present obstacles in implementing Flood Early Warning System (FEWS) in the basin. Second, we employ open-source hazard, exposure, and vulnerability datasets to assess and map potential flood impacts. Finally, we combine these two components to develop an approach for spatial planning of potential preparatory and early actions. The resulting spatial action plan can strengthen community's responsive capacity, support effective communication and dissemination of warning messages. It also reduces flood impacts and enhances existing protocols and plans, thereby advancing third and fourth pillars of FEWS. The simplicity and adaptability of our combined methodological approach make it applicable for data-scarce basins globally. Future research could explore the operationalization of the created spatial action plan in rural areas, collaboratively with local authorities and relevant stakeholders.